PERENCANAAN APRON PADA TAHUN 2038 MENGGUNAKAN METODE REGRESI LINEAR DI BANDAR UDARA H. HASAN AROEBOESMAN ENDE - Muchammad Ilham Saifud’diin; Fahrur Rozi; Supriadi (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Hasan Aroeboesman Airport Ende located Tetandara Village, South Ende Subdistrict, Ende Regency that is organized by The Ministry of Transportation. At the moment H. Hasan Aroeboesman Airport Ende is a class II Airport Unit. The existing condition of this airport is it has an apron with the dimension of 225 m x 40 m and ATR 72-600 as its critical aircraft operating. Currently, Ende is a regency that is growing quite rapidly. This can be evidenced by the movement of people in and out of the regency. One of the node of people’s movement is at H. Hasan Aroeboesman Airport Ende. To accommodate the movement of people, the necessary improvement of airport facilities is needed. Some of airport facilities that should have an improvement is the extension of the apron. The purpose of this research is to identify the actual need of apron at H. Hasan Aroeboesman Airport Ende that can be sufficient for traffic increase that will occur in the future. Based on the analysis and calculation that has been done, the dimensions of the apron expansion of 12.497,4 m2 was obtained, with 2 Boeing 737-500, and an ATR 72-600 aircraft. As the result of the calculation 55.0 of PCN would be established based on the calculation with FAARFIELD 2.0.3 and COMFAA 3.0 software.